The light of days : the untold story of women resistance fighters in Hitler's ghettos - Batalion, Judith; Conkling, Winifred (Harper, 2020)
Presents a historical account of a group of Jewish women known as the "ghetto girls" who fought in the Polish resistance during World War II, and details how their actions helped fight the Nazis and save Jewish lives. Includes black-and-white photographs, a map, and additional resources.